Personal Branding and it’s Impact for Psychologist Career in Samarinda - Irma Alfina; Indo Sennang; Alfiesyahrianta Habibie (LPPM Universitas 17 Agustus 1945 Samarinda, 2026)
Research examining personal branding among psychologists in Indonesia remains limited, particularly in regional contexts such as East Kalimantan. In the digital era, psychologists are increasingly required not only to demonstrate professional competence but also to establish strong professional visibility and credibility through effective personal branding. This study aimed to examine the effect of personal branding on career growth among psychologists in Samarinda, East Kalimantan. A quantitative correlational design was employed using purposive sampling techniques. The participants consisted of 42 active psychologists who met the inclusion criteria, including possession of a professional practice license and a minimum of one year of professional experience. Data were collected using the Personal Branding Scale adapted from Gorbatov, Khapova, and Lysova (2019) and the Career Growth Scale (CGS) developed by Weng and McElroy (2016). Data analysis was conducted using Pearson correlation and simple linear regression analyses. The results demonstrated that personal branding had a positive and significant effect on career growth (t = 8.197, p = .007, R² = .17), indicating that personal branding contributed 17% to the variance in psychologists’ career growth. Partial correlation analysis further revealed that strategic self-presentation (r = .439, p = .004), differentiation (r = .394, p = .010), and technology utilization (r = .340, p = .028) were significantly associated with career growth. These findings suggest that stronger personal branding is associated with higher professional development and broader career opportunities among psychologists. Practically, this study highlights the importance of enhancing professional visibility, digital networking, reputation management, and strategic use of social media as essential components of career development for psychologists in the contemporary digital landscape.